Effect of organic pollutants on the set point of streaming current control system - ZHANG Yan; CUI Fu-yi (浙江大学学报. 农业与生命科学版)
The streaming current control method provides a potential technique for coagulant dosage system. To evaluate its application in polluted water, the set point of streaming current control system as affected by organic pollutants was studied for the first time. The experiment was performed with four kinds of polluted water in a semi-batch reactor. It was found that the pollutants in water made the set point of streaming current control system rise, but the effect was not so notable and can be accepted when CODMn of the water resource didn't exceed 10 mg/L. Data presented here may serve as reference when the of streaming current automatic control method for coagulant dosage system is to be adopted in polluted water.